Social risk factors and outcome analysis of poisoning in an Iranian referral medical center: A toxico-epidemiological approach - Ali Mohammad Sabzghabaee; Marzieh Soleimani; Ziba Farajzadegan; Sarah Hosseinpoor; Seyyed Mohammad Mahdy Mirhosseini; Nastaran Eizadi-Mood (Wolters Kluwer Medknow Publications, 2013)
Objective: Suicide is the second major reason of death in the age range of 15-24 and is the eighth reason for overall death of adults. Because of high accessibility of people to different medications in our society, one of the easiest ways for suicide is intentional self-poisoning with medications. Therefore, the aim of this study was to determine the rate of suicide with respect to influencing social factors on patients with intentional self-poisoning. Methods: This was an analytic-descriptive prospective study. All study data were collected through a checklist in patients with intentional self-poisoning who had been referred to referral hospital within 2011-2012. Findings: A total of 400 patients (60% female) were evaluated. Age average ± standard deviation of participants was 22.57 ± 9.20 years. About 78.2% had high school degree or less. Nearly 27.8% of all happened suicides take place as a result of family disputes, marital problems (21%) and poverty (11.5%). Love issues with a rate of 10.3% were set in the next step. About 23.2% had a history of a past psychological disorder. Around 97.5% of the patients survived. The shorter the time of hospitalization is for each patient, the better survival rate is obtained through post-suicidal medical care. A statistically meaningful relationship was observed between self-poisoning to commit suicide and absence of academic education (P = 0.02). Conclusion: Suicide attempt through self-poisoning is more common in female, married individuals, people without academic education and those with a poor socio-economic status. Furthermore, results announce family disputes as the most pre-disposing factor for suicide.